How Social Considerations Improve the Equity and Effectiveness of Ecosystem Restoration. (14th December 2022) - Löfqvist, Sara; Kleinschroth, Fritz; Bey, Adia; de Bremond, Ariane; DeFries, Ruth; Dong, Jinwei; Fleischman, Forrest; Lele, Sharachchandra; Martin, Dominic A; Messerli, Peter; Meyfroidt, Patrick; Pfeifer, Marion; et al.
Abstract: Ecosystem restoration is an important means to address global sustainability challenges. However, scientific and policy discourse often overlooks the social processes that influence the equity and effectiveness of restoration interventions. In the present article, we outline how social processes that are critical to restoration equity and effectiveness can be better incorporated in restoration science and policy. Drawing from existing case studies, we show how projects that align with local people's preferences and are implemented through inclusive governance are more likely to lead to improved social, ecological, and environmental outcomes. To underscore the importance of social considerations in restoration, we overlay existing global restoration priority maps, population, and the Human Development Index (HDI) to show that approximately 1.4 billion people, disproportionately belonging to groups with low HDI, live in areas identified by previous studies as being of high restoration priority. We conclude with five action points for science and policy to promote equity-centered restoration.